Acrylic acid -co- sodium acrylate copolymers synthetized in supercritical carbon dioxide: Is it possible to pre-neutralize polymers at high pressure? - Meleán Brito, Ramses Segundo (2024)
This study focuses on the polymerization of acrylic acid together with sodium acrylate, commonly performed in traditional solvents, using supercritical carbon dioxide. This compressed polymerization solvent offers benefits like producing pure, dry polymers by a simple depressurization process. Thermally initiated free-radical polymerizations in supercritical CO2 were carried out, aiming to obtain a pre-neutralized polymer at the end of the reaction. The impact of sodium acrylate content on polymer physicochemical properties was analyzed. Conversions ranged from 86.9% to 96.7%, and sodium acrylate incorporation was verified using various analytical methods. The polymerizations displayed characteristic molar mass distributions, indicating continuous and dispersed phase polymerizations. Additionally, rheological measurements of polymer aqueous solutions revealed that viscosity increased with higher average molar mass and was responsive to pH and the presence of monovalent and divalent ions. This CO2-based approach presents a promising method for clean and safe polymer production.